Subcellular localization of the large subunit of Mo1 (Mo1 alpha; formerly gp 110), a surface glycoprotein associated with neutrophil adhesion. - Todd, R F (1984)
Mo1 alpha (formerly gp 110) is a neutrophil glycoprotein whose deficiency is associated with abnormalities in several neutrophil functions, including defects in adherence, chemotaxis, and phagocytosis. Examination of whole cells and subcellular components by the use of both immunological and electrophoretic techniques demonstrated that Mo1 alpha was located primarily in the specific granules but that a small portion was present in the plasma membrane, where it is exposed to the extracellular environment and can bind to anti-Mo1 antibody. During degranulation, Mo1 alpha is translocated from the specific granules to the plasma membrane, resulting in a 5-10-fold increase in the surface expression of this glycoprotein. These findings plus previous work suggest that plasma membrane-associated Mo1 alpha is needed for a normal interaction between neutrophils and underlying surfaces, and raise the possibility that the increase in surface adhesiveness of neutrophils that have discharged their specific granules might be due in part to the increase in the amount of Mo1 alpha in the plasma membranes of these degranulated cells.